Achieving a resilient future for small states : Caribbean 2050 - Lewis-Bynoe, Denny (Commonwealth Secretariat LondonGB, 2016)
Seeks to answer questions to policymakers such as, do current development strategies set the region on a path to achieve sustainable development? what happens if the region continues on its current policy path? is the region positioned to capitalise on the use of its limited resources and emerging opportunities? Offers strategies that will seek to balance the concerns of survivability today and sustainability tomorrow, with a focus on a long enough period to affect necessary changes; recapture the potential of young people across the Caribbean; renew and re-energise the focus on the need to secure the energy requirements of the region; and address the need for a truly transformational system of goverance across the region, while strengthening systems that safeguard against corruption and ineffectiveness.